Perbandingan Simpanan Karbon, Serapan Karbon Dioksida dan Produksi Oksigen pada Hutan Konservasi dan Hutan Produksi di Kota Palangka Raya: Comparison of Carbon Stock, Carbon Dioxide Sequestration, and Oxygen Production in Conservation Forests and Production Forests in Palangka Raya City - Ajun Junaedi; Raden Mas Sukarna; Penyang; Nuwa; Moh Rizal; Hari Paskah Saputra (JURNAL HUTAN TROPIKA, 2026)
This study aims to analyze the comparison of species composition, stand density, Shannon–Wiener diversity index, and the estimated biomass stock, carbon stock, CO₂ sequestration, and O₂ production of vegetation in conservation forests and production forests in Palangka Raya City. The analysis includes species composition, stand density, Shannon–Wiener diversity index, as well as estimates of biomass stock, carbon stock, CO₂ sequestration, and oxygen production. The results show that the number of vegetation species recorded was higher in dense vegetation cover than in sparse vegetation cover, with diversity indices ranging from low to moderate. Stand density was dominated by the sapling stage, indicating a normal regeneration pattern. The potential biomass and carbon stock of vegetation in conservation forests were higher (538.321 tons/ha and 253.011 tons C/ha) than in production forests (427.786 tons/ha and 201.059 tons C/ha). CO₂ sequestration was also greater in conservation forests (928.551 tons CO₂/ha) than in production forests (737.888 tons CO₂/ha). O₂ production showed a similar pattern, with higher values in conservation forests (675.539 tons O₂/ha) than in production forests (536.828 tons O₂/ha). Dense vegetation and the tree growth stage contributed the most to all parameters. These results confirm that vegetation structure and stand density strongly influence forest ecosystem functions in climate change mitigation..